KEBIJAKAN REDAKSIONAL SURAT KABAR FLORES POS DALAM MEMPERTAHANKAN EKSISTENSI - Kedoh, Lodowik Nikodemus (Universitas Merdeka Malang, 2018)
Abstract Flores Pos is one of the most popular and historic newspapers in the province of East Nusa Tenggara (NTT). This newspaper is very well known, accepted and made as one of the information references. Until now, Flores Pos is still present and able to survive in the midst of media competition and the development of information technology, although the appearance is still old-fashioned. This fact requires the editor of Flores Pos to determine the editorial policy of their institutions in order to be able to survive in the competition. This study aims to find out how Flores Pos editorial policy in maintaining its existence. This research uses descriptive qualitative analysis method used in this study and uses descriptive data that presents written and oral words from the subject and observable behavior. This research requires informants to obtain data and facts from a phenomenon. The object of this research is the Flores Pos newspaper. For data collection using direct observation, interviews, and literature studies. While at the stage of data analysis it is carried out through data collection, reducing data, presenting data and making conclusions. The findings in the study show that, 1) Editor of Flores Pos has the concept of editorial policy that has been designed and used for a long period of time. 2) In its reporting, Flores Pos chose to accommodate the interests of the community. 3) In maintaining its existence, the editor of Flores Pos seeks to always prioritize the power of its reporting and choose not to converge media. 4) Flores Pos adheres to its idealism and vision and mission as guidelines for internal policies that are umbrella in the Press Law and Journalistic Code of Ethics. Keywords: editorial policy, newspaper content, existence.DOI :Â https://doi.org/10.26905/nomosleca.v4i2.2547